Поддержка происходящих преобразований школы посредством развития профессионального сетевого сообщества - Антощук, Л.А. (My University, 2016)
Relevance: Nowadays teachers and other colleagues’ network activities became one of the most important topics connected with transformation in educational system. Teacher network community is a new form of professional developing. Network communities try to do their best to solve some serious problems in education. Due to the professional network communities every teacher gets an opportunity to communicate with each other, to solve actual professional issues can realize himself and promotes his professional level. Creating of network communities will provide access to new ideas and knowledge for productive teaching of younger generation. Goal: Exchange of experience, the support and cooperation, the dissemination of successful pedagogical practices, improvement of the professional level and support new technologies are oriented point in our educational system. Method: Analytic method. Scientific method. Experimental method. Result: Development of cooperation between teachers and schools for a long term process, participation in testing of the proposed ideas with further analysis of advantages and disadvantages, development of the processes of coaching and mentoring, realization of creative teachers’ potential through the presentation and publication of materials of the positive experience. Conclusion: Taking part in pedagogical communities every teacher has an opportunity to study and acquire some knowledge, skills and quality which are very necessary to a modern man, who wants to obtain some new information on a topic of interest, to get expert advice, to have access to methodological data base, to communicate with colleagues at various forums, to publish their works, to take part in professional and international competitions.
Keywords: professional network community; transformation of school practice; initiative; stimulation; oriented point